Time Course of Hemodynamic Responses to Different Doses of Lipopolysaccharide in Unanesthetized Male Rats - Brognara, Fernanda (Front Physiol, 2019)
Lipopolysaccharide (LPS) administration is a well-known method to induce systemic inflammation widely used for investigating new therapeutic strategies for sepsis treatment, which is characterized by clinical manifestations such as tachycardia and hypotension. However, there are different doses of LPS used in several studies, and the hemodynamic responses were not always well characterized. Thus, the present study aimed to evaluate the arterial pressure, heart rate, heart rate variability, and baroreflex function from rats, over time, to different doses of LPS. Femoral artery and vein catheters were inserted into anesthetized Wistar-Hannover male rats for arterial pressure recording and LPS administration, respectively. On the next day, the arterial pressure was recorded before and after (90, 180, and 360 min) LPS injection (0.06, 20, 30, and 40 mg/kg). All doses of LPS tested increased the heart rate and decreased baroreflex sensitivity over time. In addition, while LPS administration of 20, 30, and 40 mg/kg increased the mean arterial pressure over time, 0.06 mg/kg decreased the mean arterial pressure at 360 min, as compared to baseline values. Furthermore, high doses of LPS decreased the power of the HF band of the cardiac interval spectrum over time, and the higher dose increased the power of the LF band. Our data indicate that high doses of LPS promote hypertensive response over time, while a low dose decreases arterial pressure. Moreover, the changes in heart rate variability and baroreflex function elicited by LPS may be not associated with arterial pressure response produced by the endotoxemia.